MOBILITAS FISIK PADA STROKE NON HAEMORAGIK EKSTERMITAS ATAS DENGAN ROM AKTIF CYLINDRICAL GRIP DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Resmi Pangaribuan; Yuri Sutri Manjani; Jemaulana Tarigan (Poltekkes Kemenkes Malang, 2021)
Stroke or Cerebrovascular Accident or CVA is a disease that attacks anyone with a very sudden occurrence and can increase with age. Growing old is a natural process of a person after going through several stages, ie neonates, toddler, praschool, adolescents, adults and the elderly. Cylindrical Grip is a functional hand exercise by gripping a cylindrical object. The study used descriptive case study method. The subjects of the study were conducted in two patients with the same case, specifically the elderly patients who had non hemorrhagic stroke with physical mobility problem. The results of the study was obtained in both patients with the decreased of physical mobility in the upper extremities of the right and the left hand. Nursing intervention and implementation were carried out by monitoring the patient blood pressure, determining the factors that related to the patient general condition, providing range of motion exercise or Cylindrical Grip by placing a roll of tissue paper to the patient who had the hand grip weakness, monitoring muscle strength, and taking the collaboration with the doctors and other health team or physiotherapist for stroke.The evaluation was carried out for 3 days and the result obtained by doing Cylindrical Grip for 3 days, namely 2 times a day, and it was found that the physical weakness of the patients with stroke were partially resolved. It is recommended to another researchers to examine more deeply about the effectiveness of providing Cylindrical Grip in accordance with the Standard Operating Procedure or SOP in the orphanages.